Development and evaluation of INT2GRATE: a platform for comprehensive assessment of the role of germline variants informed by tumor signature profile in Lynch syndrome - Isidro, Raymond A.; Chittenden, Anu; Walker, McKenzie; Schwartz, Alison; Koeller, Diane R.; Hayes, Connor P.; Unal, Busra; Manam, Monica Devi; Buehler, Ryan M.; Manning, Danielle K.; Sholl, Lynette M.; Redston, Mark S.; et al. (Frontiers in Oncology, 2024)
The presence of variants of uncertain significance (VUS) in DNA mismatch repair (MMR) genes leads to uncertainty in the clinical management of patients being evaluated for Lynch syndrome (LS). Currently, there is no platform to systematically use tumor-derived evidence alongside germline data for the assessment of VUS in relation to LS. We developed INT2GRATE (INTegrated INTerpretation of GeRmline And Tumor gEnomes) to leverage information from the tumor genome to inform the potential role of constitutional VUS in MMR genes. INT2GRATE platform has two components: a comprehensive evidence-based decision tree that integrates well-established clinico-genomic data from both the tumor and constitutional genomes to help inform the potential relevance of germline VUS in LS; and a web-based user interface (UI). With the INT2GRATE decision tree operating in the backend, INT2GRATE UI enables the front-end collection of comprehensive clinical genetics and tumor-derived evidence for each VUS to facilitate INT2GRATE assessment and data sharing in the publicly accessible ClinVar database. The performance of the INT2GRATE decision tree was assessed by qualitative retrospective analysis of genomic data from 5057 cancer patients with MMR alterations which included 52 positive control cases. Of 52 positive control cases with LS and pathogenic MMR alterations, 23 had all the testing parameters for the evaluation by INT2GRATE. All these variants were correctly categorized as INT2GRATE POSITIVE. The stringent INT2GRATE decision tree flagged 29 of positive cases by identifying the absence or unusual presentation of specific evidence, highlighting the conservative INT2GRATE logic in favor of a higher degree of confidence in the results. The remaining 99% of cases were correctly categorized as INCONCLUSIVE due to the absence of LS criteria and >1 tumor parameters. INT2GRATE is an effective platform for clinical and genetics professionals to collect and assess clinical genetics and complimentary tumor-derived information for each germline VUS in suspected LS patients. Furthermore, INT2GRATE enables the collation of integrated tumor-derived evidence relevant to germline VUS in LS, and sharing them with a large community, a practice that is needed in precision oncology.